2018
DOI: 10.12688/f1000research.16452.1
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Double penile fracture

Abstract: Penile fracture is an underreported surgical emergency. It usually occurs as a single rupture of the tunica albuginea in one of two corpora cavernosa; a rupture of both masses is an uncommon finding. We report a case of a young male who presented to the emergency department two hours after sustaining penile trauma. Prompt surgical exploration was performed four hours post-injury. He was found to have one fracture on each corpora cavernosa, without urethral injury, which were repaired successfully. The patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The importance of penile degloving, in this case, was for a comprehensive search to check any missed injuries [18] . This technique was also described previously in which circumferential incision proximal to the coronal sulcus establishes complete degloving of the penis [19] .…”
Section: Clinical Discussionmentioning
confidence: 99%
“…The importance of penile degloving, in this case, was for a comprehensive search to check any missed injuries [18] . This technique was also described previously in which circumferential incision proximal to the coronal sulcus establishes complete degloving of the penis [19] .…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Even in the delayed presentation, delayed surgery also showed the satisfactory outcome (11,12). For the penile fracture with urethral injury, bilateral corporal rupture should also be investigated when doing the surgery repair (13,14). On the long-term follow-up, most of the patients maintained their normal erectile and voiding functions without complications after reconstruction of both corpora cavernous and urethra (15,16) (Table 1).…”
Section: Discussionmentioning
confidence: 97%
“…Other authors go even further to say that even when seen late, surgery has also shown a satisfactory result [8] [10]. For fractured corpora cavernosa with urethral injury, bilateral rupture should also be sought intraoperatively [11]. In long-term follow-up, most patients maintained normal erectile and micturition function without complications after bilateral cavernorraphy and urethral repair [12] [13].…”
Section: Discussionmentioning
confidence: 99%